THE EFFECT OF RELATIONSHIP MARKETING STRATEGIES ON CUSTOMER LOYALTY IN ISLAMIC BANKS - Muhammad Ridha Fuady (GREET, 2025)
This study investigates the effect of relationship marketing strategies on customer loyalty in Islamic banks, where trust, transparency, and adherence to Sharia principles are central. Using a descriptive-analytical research design with a mixed-methods approach, data were gathered from 500 customers across Indonesia through structured questionnaires and semi-structured interviews, analyzed with descriptive statistics, regression analysis, and thematic analysis. Findings reveal a strong positive correlation (r = 0.72, p < 0.01) between strategies such as personalized communication, customer engagement initiatives, and loyalty programs with customer loyalty, with trust emerging as the most influential factor (M = 4.5), followed by customer satisfaction (M = 4.4) and perceived value (M = 4.3). Case evidence, such as Bank Syariah Mandiri’s loyalty program, demonstrated a 25% increase in customer satisfaction and a 15% growth in referrals, while technology adoption, especially mobile banking and CRM systems, and community-oriented CSR programs further strengthened customer bonds. These results align with relationship marketing theory emphasizing relational over transactional value, concluding that Islamic banks can achieve sustainable loyalty and competitive advantage by integrating ethical practices, innovative Sharia-compliant products, digital engagement, and socially responsible initiatives.